Disability in the Hebrew Bible : interpreting mental and physical differences - Olyan, Saul M. (Cambridge ; New York : Cambridge University Press, 2008)
This book is about mental and physical disability in the Hebrew Bible.
Chapter 1 : Constructions of beauty and ugliness -- Chapter 2 : Physical disabilities classified as "defects" -- Chapter 3 : Physical disabilities not classified as "defects" -- Chapter 4 : Mental disability -- Chapter 5 : Disability in the prophetic utopian vision -- Chapter 6 : Non-somatic parallels to bodily wholeness and "defect" -- Chapter 7 : Exegetical perpetuations, elaborations and transformations : the case of Qumran "defects" in the Dead Sea scrolls.
Includes bibliographical references (pages 164-170) and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Dead Sea scrolls; Bible; Dead Sea scrolls; People with disabilities in the Bible; People with disabilities in rabbinical literature; Bible; Disabled Persons; Attitude to Health; Judaism; People with disabilities in the Bible; People with disabilities in rabbinical literature; RELIGION -- Judaism -- Sacred Writings; RELIGION -- Biblical Studies -- Old Testament; People with disabilities in rabbinical literature; People with disabilities in the Bible; Electronic books; Criticism, interpretation, etc; Electronic books